Kompetensi Dosen dan Mahasiswa dalam Metodologi Penelitian Pendidikan Matematika: Usaha Mempertajam Kualitas Penelitian Pendidikan Matematika - Agusmanto J.B. Hutauruk; Christina Purnamasari K. Sitepu; Ruth Mayasari Simanjuntak (Universitas Swadaya Gunung Djati, 2025)
Student competence in conducting final research projects and supervisor competence in mentoring research are critical aspects that need enhancement. This study aimed to analyze the competence of supervisors and students in the methodology of mathematics education research. The research was part of a broader effort to enhance the quality of mathematics education research outcomes at the higher education level. The research methodology employs descriptive analysis, with respondents comprising supervisors and students engaged in thesis research within mathematics education programs. The findings revealed that supervisors' competence in research methodology remains suboptimal. The highest competence areas include understanding instrument validity and reliability, research hypothesis formulation, and collaborative research skills, with an average achievement rate of 66.7%. Similarly, students' understanding and application of research methodology are also insufficient, with the highest competence observed in differentiating between quantitative and qualitative research at 83.25%. Factors influencing research methodology competence for both supervisors and students were identified. These include a basic understanding of research (34.4%) and, notably, the lowest level of competence in sampling techniques (25.8%). The results highlight the need for further studies aimed at enhancing and refining research methodology competencies in mathematics education.